Strengthening Students' Problem-Solving Skills Through Project Based Learning Models Based on Environmental Issues in the Era of Sustainable Education - Jumaidin, Jumaidin; Sabrina, Sabrina; Muhammad, Muhammad; Saverianus Harjoko (STKIP Taman Siswa Bima, 2025)
The ongoing environmental degradation has become a serious challenge that must be addressed through early education. At the elementary school level, students need to be equipped not only with academic knowledge but also with 21st-century skills such as critical thinking, collaboration, and problem-solving that are relevant to real-life situations. Unfortunately, classroom learning remains largely conventional and lacks contextual relevance to environmental issues surrounding students. This study aims to enhance students’ problem-solving skills through the implementation of the Project Based Learning (PjBL) model based on environmental issues. The subjects of the study were 30 fifth-grade students at SDI Negeri 1 Mamboro. The method used was quantitative with a quasi-experimental design involving one experimental group without a control group. The research instruments included pretest and posttest assessments, observation sheets, and student reflection journals. The results indicated a significant improvement in students’ problem-solving skills, with the average pretest score rising from 50.6 to 82.3 in the posttest. The paired sample t-test yielded a significance value (p < 0.05), indicating the effectiveness of the PjBL model in improving students’ critical and reflective thinking related to environmental problems. Qualitative data further supported these findings by showing increased active participation, collaboration, and environmental awareness among students. However, the study has a design limitation due to the absence of a control group, so the results should be interpreted with caution. Overall, PjBL based on environmental issues has proven to be an effective approach in fostering competencies and sustainable education values at the elementary school level.